Eliciting the antitumor immune response with a conditionally activated PD‐L1 targeting antibody analyzed with a quantitative systems pharmacology model - Alberto Ippolito; Hanwen Wang; Yu Zhang; Vahideh Vakil; Hojjat Bazzazi; Aleksander S. Popel (Wiley, 2024)
Abstract Conditionally activated molecules, such as Probody therapeutics (PbTx), have recently been investigated to improve antitumoral response while reducing systemic toxicity. PbTx are engineered to be proteolytically activated by proteases that are preferentially active locally in the tumor microenvironment (TME). Here, we perform an exploratory study using our recently published quantitative systems pharmacology model, previously validated for other drugs, to evaluate the effectiveness and targeting specificity of an anti‐PD‐L1 PbTx compared to the non‐modified antibody. We have informed the model using the PbTx dynamics and pharmacokinetics published in the literature for anti‐PD‐L1 in patients with triple‐negative breast cancer (TNBC). Our results suggest masking of the antibody slightly decreases its efficacy, while increasing the localization of active therapeutic component in the TME. We also perform a parameter optimization for the PbTx design and drug dosing regimens to maximize the response rate. Although our results are specific to the case of TNBC, our findings are generalizable to any conditionally activated PbTx molecule in solid tumors and suggest that design of a highly effective and selective PbTx is feasible.